The conquest of the Holy Land by balā% al-Dīn - Brewer, Keagan, author.
1 online resource (xx, 278 pages).
Keywords: The Libellus de expugnatione Terrae Sanctae per Saladinum (or Little Book about the Conquest of the Holy Land by òSalāòh al-Dīn) is the most substantial contemporary Latin account of the conquest of the Kingdom of Jerusalem in 1187. Seemingly written by a churchman who was in Jerusalem itself when the city was besieged and captured, the Libellus fuses historical narrative and biblical exegesis in an attempt to recount and interpret the loss of the Holy Land, an event that provoked an outpouring of grief throughout western Christendom and sparked the Third Crusade. This book provides an English translation of the Libellus accompanied by a new, comprehensive critical edition of the Latin text and a detailed study in the introduction.